Effects of Matricaria chamomilla flower extract on hepatotoxic effect of 5-fluorouracil in rabbits - Ghazi, Shayma (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objective: Matricaria Chamomilla extract has profound biological and pharmacological properties and it has been widely used for its medicinal effects. It may be helpful in preventing hepatic damage induced by drugs. The chemotherapeutic agent 5-FU has been widely used for solid types of cancer however, liver toxicity is one of its serious side effects. The present study was designed to evaluate the effectiveness of Matricaria Chamomilla flower extract for hepatotoxicity induced by administration of 5-FU into rabbits. Methods: A total number of 20 rabbits were randomly divided in to four groups, group 1 received distilled water, group 2 treated with chamomile extract (100mg/kg/day),group 3 and 4 animals were injected with 20mg/kg/day of 5-FU for 5 consecutive days and on day 6 started to receive treatment with either distilled water or chamomile extract that continued up to day 14, in which animals were sacrificed to get liver samples for histopathological analysis. A Kruskal-Wallis H and Post-Hoc tests were used for the statistical analysis and comparisons between the groups. Results: The histopathological study showed significant inflammation of hepatic tissue in the group using 5-FU compared to control and chamomile treated groups.However, using chamomile after 5-FU induced hepatotoxicity didn’t show any significant reduction of inflammation of the hepatic tissue when compared to 5-FU treated group. Conclusion: Although chamomile has profound biological and pharmacological properties such as anti-inflammatory and antioxidant activities that may be helpful in preventing hepatotoxicity induced by some drugs but in this study it didn’t show effectiveness in treating 5-FU induced hepatotoxicity at the dose and duration used.